PACKAGING OF NATURE AND CULTURAL CONSERVATION ACTIVITIES THROUGH ECOTOURISM TITLED FESTIVAL - Ahmad Kurniawan; Enok Maryani; Rini Andari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
The problem of protecting the environment is often not considered properly. Including the maintenance and management of the Sekanak Lambidaro River in Palembang, which was once a garbage dump and surrounded by slums. So it certainly makes damage to the place of an ecosystem of flora and fauna that exist in the environment. Not to mention that the endless cultural conflicts between the Sekanak River area have become a problem in the city of Palembang. So, a Sekanak Lambidaro Palembang River Festival was held in order to make the community affected by the bad environment more livable. Through activities that are oriented towards a green environment based on the concept of sustainable development. This concept is used so as not to make people continue to be influenced by the great world of globalization at the moment. By using a descriptive qualitative research method with the aim of being able to find out how useful this festival is in increasing the awareness of the people of Palembang City in nature and cultural conservation by applying the principles of ecotourism and sustainable tourism.